Tax in the digital age: is South Africa's current income tax legislation adequate for the taxation of the digital economy and e-commerce? - De Abreu, De Abreu Gabriela (My University, 2019)
The purpose of this research report is to examine South Africa’s current income tax legislation and determine whether or not it is appropriate for taxing the digital economy and related transactions and activities i.e. e-commerce. In particular this research report focuses on the source rules and the application of double tax agreements in respect of the permanent establishment concept, found in South Africa’s income tax legislation, when applied to the digital economy and e-commerce. This research report critically analyses the solutions being pursued in other jurisdictions by legislators, tax administrators and international organisations and how these possible solutions could be considered and implemented into South African tax legislation.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Law
Keywords: Taxation--Law and legislation--South Africa; Income tax--South Africa